Obstetric outcome in homeless women. Issue 6746 (4th August 1990) - Paterson, C M; Roderick, P
Abstract : OBJECTIVE–To characterise the pregnant homeless population booking and delivering at St Mary's Hospital, London, and ascertain whether their obstetric outcome was adversely affected by their homeless condition. DESIGN–Retrospective comparison of demographic characteristics of 185 homeless women booking for delivery with those of housed women booking in the same period and with the population of North West Thames region; comparison of obstetric performance of homeless women with subgroup of the housed population (group matched for age, parity, and ethnic origin). SETTING–Consultant obstetric unit, St Mary's Hospital, London. SUBJECTS–All women booking between April 1987 and March 1988 who subsequently had a registrable birth. MAIN RESULTS–185 (8%) Of the 2308 women studied were homeless. Compared with the housed population, they had a larger proportion of young women, women of high parity, and Indo-Pakistani women and a smaller proportion of primiparas. Homeless women booked later and had had more previous obstetric problems than housed women. Pregnancy outcome (assessed by birth weight and prematurity rates) was worse than that of both women housed locally and the regional population. Antenatal attendance, complications, intrapartum performance, and perinatal outcome of homeless women did not differ from those in the control group. CONCLUSIONS–This study has been unable to show any significant differences in the outcome of pregnancy in homeless women that can be directly attributed to living in bed and breakfast accommodation, but these women have sociodemographic characteristics and obstetric risk factors that contribute to a poorer outcome in pregnancy than for the general population.